1981
DOI: 10.1007/bf00596172
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP inhibits contractility of detergent treated glycerol extracted cardiac muscle

Abstract: Glycerinated myocardial fibres treated with a detergent (Lubrol WX) and suspended in ATP salt solution produce half maximum isometric tension at pCa 6.2 (at pH 6.7). After addition of cyclic AMP (1-100 microM), the pCa required for half maximum activation is 5.9. c-AMP in concentrations of 1-100 microM induces a dose dependent inhibition (up to 40% at pCa6), and this effect can be amplified by the phosphodiesterase inhibitor IBMX (3-isobutyl-1-methylxanthine) 10(-4) M. The effect is similar in presence and abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 22 publications
4
22
0
Order By: Relevance
“…Similar ®ndings have been reported for levosimendan in healthy humans (Sundberg et al, 1995). It is possible that exercise-induced increments in b-adrenergic activity, via cAMP-mediated phosphorylation of troponin-l, neutralizes the levosimendan or EMD 57033-mediated increases in Ca 2+ responsiveness of the myo®laments (Herzig et al, 1981). In the present study, EMD 57033 produced an increase in contractility at all levels of exercise in the presence of b-adrenoceptor blockade, which is consonant with the hypothesis that during exercise in the normal heart a pharmacologically-induced increase in myo®lament sensitivity to Ca 2+ can be o set by very high levels of b-adrenergic activity.…”
Section: Haemodynamic Actions Of Emd 57033 During Treadmill Exercisesupporting
confidence: 80%
“…Similar ®ndings have been reported for levosimendan in healthy humans (Sundberg et al, 1995). It is possible that exercise-induced increments in b-adrenergic activity, via cAMP-mediated phosphorylation of troponin-l, neutralizes the levosimendan or EMD 57033-mediated increases in Ca 2+ responsiveness of the myo®laments (Herzig et al, 1981). In the present study, EMD 57033 produced an increase in contractility at all levels of exercise in the presence of b-adrenoceptor blockade, which is consonant with the hypothesis that during exercise in the normal heart a pharmacologically-induced increase in myo®lament sensitivity to Ca 2+ can be o set by very high levels of b-adrenergic activity.…”
Section: Haemodynamic Actions Of Emd 57033 During Treadmill Exercisesupporting
confidence: 80%
“…The decrease in Ca2+ sensitivity of contractile elements by isoprenaline is due to cyclic AMP-dependent phosphorylation of troponin I as reported previously (Ray & England, 1976;Solaro et al 1976;McClellan & Winegrad, 1978;Mope, McClellan & Winegrad, 1980;Herzig et al 1981;Yamamoto & Ohtuki, 1982;Kranias et al 1985). The decrease in Ca2+ sensitivity, estimated using the tetanic contraction, appeared at about 10-8 M at which significant change in TR50 was observed.…”
Section: Ji-adrenoceptor Stimulation In Cardiac Muscles 233mentioning
confidence: 58%
“…A decrease in the Hill coefficient by isoprenaline which is not reported in the sarcolemma-free preparations is due to a change in the intracellular ionic environment produced following an increase in cyclic AMP concentration (McClellan & Winegrad, 1978;Mope et al 1980;Herzig et al 1981). The decline of tonic tension in tetanus in the presence of isoprenaline might be also due to the change in the intracellular ionic environment (for example H+).…”
Section: Relationship Between [Ca2+]i and Tension In Tetanic Contractionmentioning
confidence: 96%
“…Papillary muscles or trabeculae from left ventricle were dissected, tied to thin glass rods, and skinned overnight in ice-cold relaxing solution (mM: imidazole, 20; pH 6.8; ATP, 7.5; MgCl 2 , 10; NaN 3 , 1; EGTA, 4; leupeptin, 0.1; BDM, 20; total ionic strength, 130) containing 0.25-0.5% Triton X-100 (26). A relatively low buffer pH used in skinned fiber mechanical studies was reported to be beneficial for the functional preservation of the regulatory system (27). After washes with fresh relaxing buffer, fiber bundles 150 -200 m thin and 3-4 mm long were mounted isometrically between a position-controlled rigid post and a force transducer (AME AE 801, Horten Electronics, Norway) with nitroacetate glue (26).…”
Section: Methodsmentioning
confidence: 99%